EXPLICATING POETRY TO DESCRIBE THE POSSIBLE MEANING OF A POEM - Feriyanti Elina Gultom (BAHAS, 2017)
Poetry is the literature that evokes a concentrated imaginative awareness of experience or a specific emotional response through language chosen and arranged for its meaning, sound, and rhythm. There are feelings, thoughts, and ideas that can be difficult to explain and analyze. Poetry is a kind of language within languages that allows people regardless of age, sex, religion, sexual orientation, and even time eras to communicate with one another. When some people hear the word "Poetry", images of unfathomable scenes, words and phrases come to mind. Poetry explication is needed to describe the possible meanings and relationships of the words, images, and other small units that make up a poem. Writing an explication is an effective way for a reader to connect a poem’s plot and conflicts with its structural features. Since each poem is unique, there is no one way of going about this, butt the elements of analyzing poetry;  to identify the meaning through its parts, give a sense of interpreting a poem: (1) Examine the structure of the poem, And (2) Examine the pattern of the poem. Key words: Explicating Poetry, Meaning of a poem.